Comparative Analysis of Metonymic Expressions in English and Karakalpak Poetry - Sh.Saymanova (European Science Publishing, 2023)
In this exploration, we delve into the intricacies of metonymy, a captivating literary device that transcends the boundaries of language and culture. Metonymy, the artful substitution of one word or phrase for another based on their close association, emerges as a powerful tool in the hands of poets. This journey will take us through the realms of both English and Karakalpak poetry, unraveling the nuances and cultural dimensions embedded within this figure of speech.
Keywords: poem, metonymy, stylistic device, meaning, description, express.